The Rise of Pornography The Need for Vigilance From All Levels of Society - B Agus Rukmono; Bobby Steven Octavianus (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Nowadays, pornography has spread to all circles of society. It turns out that pornography is not only a consumption of young people or teenagers, but also a problem for adults. However, most scientific journals discuss the issue of pornography in relation to young people. It is as if pornography is only a youth problem. From the data obtained, it turns out that many adults also access pornography and not a few are already at the level of addiction. Even those who are supposed to be the guardians of morality, such as educators and the clergy, have problems in this regard, as Pope Francis has stated. Therefore, pornography has become a community problem that should be a common concern and should be handled together. In this article, the author tries to raise the issue of pornography, which has become a problem for all members of society. The research method taken is by using a literature study. The data is analyzed using the Interpretative Phenomenological Analysis (IPA) approach. As a theoretical framework to help the analysis, the author uses religious, moral, and social ethics theories and touches on psychological approaches. With this, the author found the impacts caused by pornography as well as efforts to deal with it.